2022
DOI: 10.2196/32614
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-Social Learning for Continuing Professional Development in Low- and Middle-Income Countries: Integrative Review

Abstract: Background Access to continuing professional development (CPD) for health care workers in low- and middle-income countries (LMICs) is severely limited. Digital technology serves as a promising platform for supporting CPD for health care workers by providing educational content virtually and enabling virtual peer-to-peer and mentor interaction for enhanced learning. Digital strategies for CPD that foster virtual interaction can increase workforce retention and bolster the health workforce in LMICs. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Our findings reinforce the growing body of evidence highlighting the benefits of utilizing digital communication tools such as WhatsApp to enhance healthcare communication and consultation, particularly in remote and rural settings (Hogan et al, 2019;Onsongo et al, 2023). Participants noted that the usage of WhatsApp can enable continuous, accessible, and efficient communication between remote rural healthcare providers and EMP, providing a practical solution to the geographical and logistical challenges often associated with healthcare delivery in such regions (Guillaume et al, 2022). These findings align with previous research suggesting that digital communication tools can facilitate improved access to expert advice, especially during critical situations (Ferri et al, 2020;Haleem et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…Our findings reinforce the growing body of evidence highlighting the benefits of utilizing digital communication tools such as WhatsApp to enhance healthcare communication and consultation, particularly in remote and rural settings (Hogan et al, 2019;Onsongo et al, 2023). Participants noted that the usage of WhatsApp can enable continuous, accessible, and efficient communication between remote rural healthcare providers and EMP, providing a practical solution to the geographical and logistical challenges often associated with healthcare delivery in such regions (Guillaume et al, 2022). These findings align with previous research suggesting that digital communication tools can facilitate improved access to expert advice, especially during critical situations (Ferri et al, 2020;Haleem et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…However, several studies mentioned that digital approaches may exacerbate inequalities (eight studies) and be less relevant in a large number of LMIC institutions with limited digital infrastructure 47–54. Additional challenges with digital tools in LMICs include power cuts and constant interruptions to internet access 55…”
Section: Resultsmentioning
confidence: 99%
“…Continuity of partnership is crucial in improving the competencies and motivation of healthcare workers whose numbers are dwindling and are sorely lacking in low- and middle-income counties. As studies have shown the effectiveness of using information and communication technology for continuing education in low- and middle-income countries [ 16 , 17 ], stronger international partnerships and collaborations can facilitate designing more effective education delivery methods that ensure sustainability and best practice.…”
Section: Discussionmentioning
confidence: 99%